CHEMICAL COMPOSITION OF THE PLANT POLYGONUM AVICULARE L. AND ITS PLACE IN FOLK MEDICINE (Scientific journal of the Fergana State University, 2024)
The article analyzes scientific data on the medicinal properties of the avicular plant (Polygonum aviculare L.), its use in folk medicine and modern medicine. Also, the amount of macro and microelements in the surface (stem, leaf, flower) and root of the plant was determined using inductively coupled plasma mass spectrometry (ICP-MS).